Van meststof tot afval, van het platteland naar de rivier: een geschiedenis van Brussel en zijn excrementen - Ananda Kohlbrenner (Brussels Studies, 2014)
During the second half of the 19th century, the River Senne became the preferred outlet for wastewater in Brussels. While at the beginning of the century, faecal matter was collected and sold to farmers as fertiliser, the gradual adoption of mains drainage had the direct effect of causing a lasting increase in pollution levels in the river. This research focuses on this transition. It questions the reasons why excrement recycling was abandoned and how the Senne became the new recipient for some of the wastewater in the capital.Through the analysis of the discussions and projects in connection with the management of faecal matter, this study is aimed at better understanding the transformations in the relationship between Brussels and its environment which took place during the 19th century. It explores the major sanitation works in Brussels by focusing on a little known aspect, i.e. the project for broad irrigation with wastewater.This article therefore highlights the role of planned or built technical infrastructures in the realisation of urban projects and the way in which the impact of Brussels on its environment was modified on a long-term basis.